Case Series of Burkholderia Pseudomallei Infections in Critically Ill Patients: Unveiling Key Challenges - Raja, Rishwanth; Sailaja, Baby K; Hemalatha, RV; Selvam, Velmurugan; Renuka, MK (Scripta Medica, 2026)
Melioidosis remains a diagnostic challenge in tropical regions due to its broad clinical spectrum. This series presents seven diabetic individuals from an endemic area with diverse forms of the disease, including pulmonary, visceral, soft tissue and lymph node involvement. Laboratory confirmation was achieved through culture and nested polymerase chain reaction (PCR). Most patients improved with appropriate intravenous therapy followed by oral antibiotics; one experienced recurrence. The varied presentations often resemble other endemic infections, delaying diagnosis. Prompt clinical recognition and early use of molecular tools are vital for initiating targeted treatment and improving outcomes in vulnerable populations.
Keywords: Melioidosis; Burkholderia pseudomallei; Polymerase chain reaction, nested; Infections; Tropical diseases, neglected